2014
DOI: 10.2484/rcr.v9i1.908
|View full text |Cite
|
Sign up to set email alerts
|

CNS toxoplasmosis in an immunocompetent individual

Abstract: Toxoplasmosis is a serious and life-threatening disease in humans with a high prevalence in immunocompromised persons. The disease has a wide spectrum, depending on the immune status of the person. A CNS manifestation of toxoplasmosis in an immunocompetent person is very rare and often undetected. Our case of CNS toxoplasmosis in an immunocompetent person emphasizes the radiological diagnosis, which was further confirmed by advanced microbiology technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Because there are various studies and case reports that showed hypointense lesions on T1-weighted MRI in toxoplasmosis. [22][23][24] However, in T2-weighted MRI, a high prevalence of hyperintense lesions was observed (79.4%). This also can be linked to the increased prevalence of toxoplasmosis in the study group, as T2-weighted MRI in toxoplasmosis shows hyperintensive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are various studies and case reports that showed hypointense lesions on T1-weighted MRI in toxoplasmosis. [22][23][24] However, in T2-weighted MRI, a high prevalence of hyperintense lesions was observed (79.4%). This also can be linked to the increased prevalence of toxoplasmosis in the study group, as T2-weighted MRI in toxoplasmosis shows hyperintensive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually present with headache, confusion, or changes in the level of consciousness, fever, focal neurological signs, and seizure [22,23]. Presentation with meningeal signs and diffuse encephalitis is less common [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral toxoplasmosis is usually associated with immunodeficiency conditions. However, the incidence of cerebral toxoplasmosis in an immunocompetent host, especially with poor nutritional hygiene, has been reported . Neuroimaging features in these patients tend to differ as the lesions are linear in morphology and are located at the grey‐white matter junction with a centripetal spread along the Virchow‐Robin spaces.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of cerebral toxoplasmosis in an immunocompetent host, especially with poor nutritional hygiene, has been reported. 11,12 Neuroimaging features in these patients tend to differ as the lesions are linear in morphology and are located at the grey-white matter junction with a centripetal spread along the Virchow-Robin spaces. Our patient was a smoker but otherwise in good health, with negative clinical or typical radiological features for toxoplasmosis; however, autopsy was confirmatory for cerebral toxoplasmosis without any evidence for immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%